Security and governance in South Asia - Chari, P. R.; Regional Centre for Strategic Studies (New Delhi : Manohar Publishers & Distributors, 2001)
Contributed articles.
Includes bibliographical references and index.
Keywords: National security -- South Asia; South Asia -- Defenses; South Asia -- Politics and government; South Asia -- Foreign relations